CROSS-CULTURAL EMPATHY IN EFL CLASSES: A DIALOGIC APPROACH TO TEACHING LITERATURE - Djihad Afaf, Selt (PUPIL: International Journal of Teaching, Education and Learning, 2024)
With the turn of the 21st century, the world has flipped into a multicultural space in which cultural gaps have been bridged by a communal sense of awareness that fostered the process of cross-cultural empathy. In the field of education, ensuring a dialogic atmosphere tends to hog the limelight of the major academics shaping a stiff bastion for effective learning pedagogies. The significance of cultural empathy in EFL classes lies in facilitating the acquisition of communicative competencies of the targeted language, through the use of a Bakhtinian dialogic approach and implementing it in the praxis of the learning atmosphere. The Primary aim of this paper is to investigate the teaching methods and the learning paradigms that allow us to measure the extent to which a dialogic approach advocates collaboration and reflexive interaction among EFL learners to increase their cultural empathy. Relying on descriptive and analytical methods, the present paper also seeks to clarify the significance of this approach in teaching literature, given the fact that literary works consist fertile grounds for diverse points of view captured through the multifaceted understanding of the interwoven links between literary texts. This research concludes that dialogism plays a pivotal role above all teaching practices as it accords a high premium on the critical scrutiny of literary texts. It suggests that, through this approach, teacher-students and students-students discussions during the analysis of texts formulate a robust booster for the English Language enhancement, ergo, cross-cultural empathy.